Hydrogen Sulfide Attenuates LPS-Induced Acute Kidney Injury by Inhibiting Inflammation and Oxidative Stress. (31st January 2018) - Chen, Yuhong; Jin, Sheng; Teng, Xu; Hu, Zhenjie; Zhang, Zhihong; Qiu, Xuan; Tian, Danyang; Wu, Yuming
Abstract : In order to investigate the protective mechanism of hydrogen sulfide (H2 S) in sepsis-associated acute kidney injury (SA-AKI), ten AKI patients and ten healthy controls were enrolled. In AKI patients, levels of creatinine (Cre), urea nitrogen (BUN), tumor necrosis factor- α (TNF- α ) and interleukin-1 β (IL-1 β ), and myeloperoxidase (MPO) activity as well as concentrations of malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) were significantly increased compared with those of controls. However, plasma level of H2 S decreased and was linearly correlated with levels of Cre and BUN. After that, an AKI mouse model by intraperitoneal lipopolysaccharide (LPS) injection was constructed for in vivo study. In AKI mice, H2 S levels decreased with the decline of 3-MST activity and expression; similar changes were observed in other indicators mentioned above. However, the protein expressions of TLR4, NLRP3, and caspase-1 in mice kidney tissues were significantly increased 6 h after LPS injection. NaHS could improve renal function and kidney histopathological changes, attenuate LPS-induced inflammation and oxidative stress, and inhibit expressions of TLR4, NLRP3, and caspase-1. Our study demonstrated that endogenous H2 S is involved in the pathogenesis of SA-AKI, and exogenous H2 S exerts protective effects against LPS-induced AKI by inhibiting inflammation and oxidative stress via the TLR4/NLRP3 signaling pathway.